2001
DOI: 10.1111/j.1479-8301.2001.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Clinical Studies on the Measurement of β‐amyloid(1–42) in Cerebrospinal Fluid as a Diagnostic Marker for Alzheimer's Disease and Related Disorders: Multi Center Study in Japan

Abstract: Background: The development of diagnostic markers for earlier and more accurate clinical diagnosis of Alzheimer's disease (AD) is essential to identify unequivocally AD patients during life. This study is to investigate the basic performance and clinical significance of P-amyloid(142) (AP42) level measurement in cerebrospinal fluid (CSF) alone or in combination with CSF tau for distinguishing AD from non-AD disorders. Methods: The basic characteristics of the reagent for measuring A&, which used Sandwich ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…An explanation for this finding could be that binding of A␤42 to albumin masked the epitope recognized by A␤42-specific antibodies (15,16 ). This binding of A␤42 to other proteins might also cause the low recovery rate of the A␤42 ELISA, although Vanderstichele et al (6 ) and others could not find interference with A␤ by other proteins, including albumin (17 ). However, interference experiments are largely dependent on the protocol being used or on whether preincubation is needed.…”
Section: Discussionmentioning
confidence: 82%
“…An explanation for this finding could be that binding of A␤42 to albumin masked the epitope recognized by A␤42-specific antibodies (15,16 ). This binding of A␤42 to other proteins might also cause the low recovery rate of the A␤42 ELISA, although Vanderstichele et al (6 ) and others could not find interference with A␤ by other proteins, including albumin (17 ). However, interference experiments are largely dependent on the protocol being used or on whether preincubation is needed.…”
Section: Discussionmentioning
confidence: 82%
“…Most studies have found normal to mildly increased CSF T-tau levels in other dementias, such as frontotemporal dementia (FTD) 14,15,21,50,52,69,70,73,[82][83][84][85][86] and Lewy body dementia (LBD). [85][86][87][88][89][90] Other than in aged nondemented individuals, normal CSF T-tau is found in depression, alcoholic dementia, and in chronic neurological disorders such as Parkinson's disease (PD) and progressive supranuclear palsy.…”
Section: Csf T-taumentioning
confidence: 99%
“…He was diagnosed as having frontotemporal dementia (FTD) in FTLD because of his disinhibited, stereotyped and repetitive behaviors, the pattern of cognitive dysfunction, and neuroimaging findings. The result of CSF tau and Aβ (tau/Aβ) did not indicate that he had AD 5 …”
Section: Case Reportmentioning
confidence: 93%
“…Neurologic examination was unremarkable except for the grasp reflexes of both hands. In the cerebral spinal fluid (CSF) general findings were normal and the levels of Tau, Aβ 42 and Tau/Aβ 42 were 244 pg/mL, 827 pg/mL and 0.30, respectively (Tau/Aβ 42 in patients with Alzheimer's disease (AD) is 1.63 ± 1.32 and in neurodegenerative disorders without AD (ND) is 0.56 ± 0.63) 5 . Electroencephalogram (EEG) was normal.…”
Section: Case Reportmentioning
confidence: 99%